2019
DOI: 10.1080/1351847x.2019.1641123
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and voluntary savings for retirement: novel causal evidence

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 65 publications
8
24
0
2
Order By: Relevance
“…Many studies assessed financial literacy based on observed financial knowledge. This one-dimensional view highlights the importance of a correct understanding of financial concepts (Boisclair, Lusardi and Michaud 2017;Cupák, Kolev and Brokešová 2019;Jappelli and Padula 2015;Lusardi and Mitchell 2011;Van Rooij, Lusardi and Alessie 2012). Observed financial knowledge can be subdivided into basic knowledge about topics such as compound interest, inflation, time value of money and monetary illusion and advanced knowledge about topics such as asset risk, long-term return, volatility, and diversification (Nguyen et al 2017;Potrich, Vieira and Mendes-Da-Silva 2016).…”
Section: C2 Measuring Financial Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies assessed financial literacy based on observed financial knowledge. This one-dimensional view highlights the importance of a correct understanding of financial concepts (Boisclair, Lusardi and Michaud 2017;Cupák, Kolev and Brokešová 2019;Jappelli and Padula 2015;Lusardi and Mitchell 2011;Van Rooij, Lusardi and Alessie 2012). Observed financial knowledge can be subdivided into basic knowledge about topics such as compound interest, inflation, time value of money and monetary illusion and advanced knowledge about topics such as asset risk, long-term return, volatility, and diversification (Nguyen et al 2017;Potrich, Vieira and Mendes-Da-Silva 2016).…”
Section: C2 Measuring Financial Literacymentioning
confidence: 99%
“…Long-term savings offer opportunities to engage in regular consumption throughout people's life cycle, and short-term or emergency savings provide purchasing power protection in the event of income shocks (Mahdzan and Tabiani 2013). Various studies have analyzed the factors that influence individuals' saving behavior and highlighted the role of financial literacy (e.g., Cupák, Kolev and Brokešová 2019;Pak and Chatterjee 2016;Ramalho and Forte 2019), which has an important function in financial decision-making, especially given the increasing complexity of financial systems (Potrich, Vieira and Mendes-Da-Silva 2016). People must acquire not only financial knowledge but also the ability and confidence to apply this expertise when making financial decisions (Huston 2010).…”
mentioning
confidence: 99%
“…The majority of empirical research on financial literacy and savings have relied on representative adult samples (Cupák, Kolev and Brokešová 2019;Ramalho and Forte 2019). Other studies have analysed students (Bongini and Cucinelli 2019; de Cecco and Estache 2016; Potrich, Vieira and Mendes-Da-Silva 2016), millennials (Yong, Yew and Wee 2018), groups with higher-than-average financial literacy such as teachers (Zulaihati, Susanti and Widyastuti 2020) and US Federal Reserve System collaborators (Clark et al 2014).…”
Section: Target Groupsmentioning
confidence: 99%
“…Long-term savings offer opportunities to engage in regular consumption throughout people's life cycle, and short-term or emergency savings provide purchasing power protection in the event of income shocks (Mahdzan and Tabiani 2013). Various studies have analyzed the factors that influence individuals' saving behavior and highlighted the role of financial literacy (e.g., Cupák, Kolev and Brokešová 2019;Pak and Chatterjee 2016;Ramalho and Forte 2019), which has an important function in financial decision making, especially given financial systems' increasing complexity (Potrich, Vieira and Mendes-Da-Silva 2016). People must acquire not only financial knowledge but also the ability and confidence to apply this expertise when making financial decisions (Huston 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Von Gaudecker (2015) found that households in The Netherlands that score high on financial literacy or rely on professional financial advice achieve better investment outcomes and more diversified portfolios. 1 Research has also documented the positive impact of financial literacy on pension savings and retirement planning (Van Rooij et al, 2012;Cupák et al, 2019).…”
Section: Financial Literacymentioning
confidence: 99%